Evaluating the extent of the response of the tax administration leaders towards the concept of the strategic lens and its relationship to tax pioneer performance: Applied Research in the General Authority for taxes (Journal of Accounting and Financial Studies ( JAFS ), 2020)
The aim of the research is to evaluate the response of the researched leaders towards practicing the concept of the lens, which is its dimensions with (stakeholders, resource mobilization, knowledge development, culture management) and the nature of its relationship to tax pioneer performance represented in its dimensions (strategic direction, leadership indicators, growth, renewal and modernization, efficiency, Effectiveness) The questionnaire was approved as a main tool in collecting data and information from the sample members in the General Authority of Taxes, which number (91) Who are on (M. General Manager, Division Director, Deputy Director, Senior Division Director, Deputy Director, Second Division, Division Officer, M. Division Officer) and the two statistical programs (SPSS) were used in calculating (the mean, standard deviation, coefficient of difference, coefficient of difference Correlation, t-test, and the research reached a number of conclusions, the most prominent of which were: The level of response of the tax administration leaders towards the practice of the strategic lens has a high degree, There is a strong, and positive correlation between the strategic lens and the dimensions of tax performance.